2017
DOI: 10.1002/2017ja024412
|View full text |Cite
|
Sign up to set email alerts
|

Solar Wind Plasma Parameter Variability Across Solar Cycles 23 and 24: From Turbulence to Extremes

Abstract: Solar wind variability spans a wide range of amplitudes and timescales, from turbulent fluctuations to the 11 year solar cycle. We apply the data quantile‐quantile (DQQ) method to NASA/Wind observations spanning solar cycles 23 and 24, to study how the uniqueness of each cycle maximum and minimum manifests in the changing statistical distribution of plasma parameters in fast and slow solar wind. The DQQ method allows us to discriminate between two distinct components of the distribution: the core region simply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 56 publications
(62 reference statements)
1
11
0
Order By: Relevance
“…For example, where two linear regions exist in a plot, one may be indicative of a core component of the distribution where the second component corresponds to the tail in the distribution. This kind of dual‐distribution QQ plot is common in space weather variables where the core of the distribution corresponds to small‐scale turbulent behavior and the tail of the distribution identifies large‐scale driven behavior (Tindale & Chapman, ). Here, we will compare the distribution of − SMR to − D ST using the QQ plot.…”
Section: Indices and Their Solar Cycle Variationmentioning
confidence: 99%
“…For example, where two linear regions exist in a plot, one may be indicative of a core component of the distribution where the second component corresponds to the tail in the distribution. This kind of dual‐distribution QQ plot is common in space weather variables where the core of the distribution corresponds to small‐scale turbulent behavior and the tail of the distribution identifies large‐scale driven behavior (Tindale & Chapman, ). Here, we will compare the distribution of − SMR to − D ST using the QQ plot.…”
Section: Indices and Their Solar Cycle Variationmentioning
confidence: 99%
“…The detailed quantification of the time variation of the statistical distribution of key space weather relevant variables is thus a topical question. The distributions of geomagnetic activity (Tanskanen et al, ) and geomagnetic indices (Campbell, ; Lockwood et al, , ) vary both within and between solar cycles (Tindale & Chapman, , ). The distributions of solar wind variables can be non‐Gaussian (Veselovsky et al, , and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…However, as Lockwood et al () note, the lognormal does not necessarily provide the best fit across the full distribution for all variables of interest. Indeed, Tindale and Chapman () found that the distribution of solar wind magnetic field can be far from lognormal. Here we will show how to test whether the functional form of the distribution of a given variable is invariant against solar cycle dependent changes, without assuming any specific functional form, lognormal or otherwise, for the underlying distribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To alternatively assess the quality of the N m F 2 estimates from RKN measurements, we performed the additional analysis by producing the so-called quantile-quantile (Q-Q) plots of the RKN and CADI/ RISR data. We adopted an approach similar to that of Tindale and Chapman (2017). The data for each of the instruments were first ranked according to reported values of the electron density and then the quantiles were selected between 5 and 95% of the total number of points with a step of 5%.…”
Section: Assessment Of Rkn Electron Density Estimates With Quantile Amentioning
confidence: 99%